The last light over Oslo : a novel - Rickloff, Alix (William Morrow, an imprint of HarperCollins Publishers, 2024)
A gripping historical novel set in Norway and Sweden in 1940, based on true events, which follows one of the first female US Ministers, Daisy Harriman, and her fictional niece as the two are unexpectedly caught up in the German invasion of Norway. Cleo Jaffray was an American. A war in Europe had nothing to do with her. She told herself that right up until the man she loved went missing in Poland and Cleo was forced to turn to the only person who might be able to help--her aunt Daisy, the US Minister to Norway. Daisy Harriman has never shied away from a challenge, be it canvassing for women's suffrage or driving Red Cross ambulances in WWI, so as only the second woman ambassador, she is determined to prove the naysayers wrong and succeed in her post. When her disgraced niece Cleo lands on her doorstep, penniless and demanding help to find her lost lover, Daisy must balance her responsibilities as a diplomat with her desire to help her family. Their search for answers is interrupted when Germany invades Norway and the two of them find themselves on the run in a countryside that is quickly becoming a battleground. Then as Daisy is given the task of escorting the Norwegian Crown Princess and her young children to America, Cleo's lover resurfaces with a story that doesn't add up and dangerous enemies on his trail. This riveting historical novel, based on the astounding life of Daisy Harriman and a real-life royal rescue, vividly captures a desperate time and a fearless heroine.